2019
DOI: 10.4103/ijabmr.ijabmr_248_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boswellia serrata extract on acute inflammatory parameters and tumor necrosis factor-α in complete Freund's adjuvant-induced animal model of rheumatoid arthritis

Abstract: Context: The worldwide prevalence of rheumatoid arthritis (RA) is about 1%, whereas in India, it is approximately 0.75%. The current therapy for RA includes nonsteroidal anti-inflammatory drugs corticosteroids, disease-modifying anti-rheumatic drugs and some recently developed biologic agents, but all of these are associated with adverse effects. Some herbal drugs, such as Boswellia serrata, have been reported to possess anti-inflammatory activity. Aims: The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 20 publications
2
15
0
1
Order By: Relevance
“…Based on the existing, the dose was obtained from previous study conducted by Kumar et al, and Sharma et al These studies investigated the anti-inflammatory effects of Boswellic acid, and the doses used were in the range 0-100 mg/kg. Since, we are studying the effect of Piper longum on the bioavailability of β-boswellic acid, we performed the study with 20 mg/kg (Sharma et al, 1989;Kumar et al, 2019;Ammon, 2016). Previous studies have indicated that the effective bioenhancing dose of piperine (Piper longum extract) for drugs varies and that a dose of approximately 10% (wt/wt) of the active drug or a daily dose of 10-20 mg/day to be regarded as an appropriate bioenhancing dose for majority of the drugs (Wadhwa et al, 2014).…”
Section: Preparation Of Animals For the Pharmacokinetic Studymentioning
confidence: 99%
“…Based on the existing, the dose was obtained from previous study conducted by Kumar et al, and Sharma et al These studies investigated the anti-inflammatory effects of Boswellic acid, and the doses used were in the range 0-100 mg/kg. Since, we are studying the effect of Piper longum on the bioavailability of β-boswellic acid, we performed the study with 20 mg/kg (Sharma et al, 1989;Kumar et al, 2019;Ammon, 2016). Previous studies have indicated that the effective bioenhancing dose of piperine (Piper longum extract) for drugs varies and that a dose of approximately 10% (wt/wt) of the active drug or a daily dose of 10-20 mg/day to be regarded as an appropriate bioenhancing dose for majority of the drugs (Wadhwa et al, 2014).…”
Section: Preparation Of Animals For the Pharmacokinetic Studymentioning
confidence: 99%
“…Boswellia Serrata has a singular anti-inflammatory property as suggest by Siddiqui [11]. Recently, the effect of Boswellia Serrata has been shown in animal model of Rheumatoid Arthritis as adjuvant to conventional therapy for contrasting the pro-inflammatory activity of Tumor Necrosis Factor-α [12]. US biometric measurements control of the patients has allowed to performe a statistical analysis that has shown reduction of edema that becomes significant after 30 post-operative days of drug treatment (p=0.043) and it's more significant after 60 post-operative days (p=0.001), underlining the benefits of this treatment also after one month of drug suspension.…”
Section: Discussionmentioning
confidence: 99%
“…This activity was confirmed by complete Freund's adjuvant-induced arthritis in wistar rats. This activity was assessed by his pathological examination and various other parameters such as ankle diameter, paw volume, and arthritis index 55 . A novel synergistic composition derived from Boswellia serrata gum resin is Aflapin.…”
Section: Kumar Et Al In Their Research Study Observed Thatmentioning
confidence: 99%